Penguatan Keterampilan Menulis Karya Ilmiah Bagi Mahasiswa Jurusan Pendidikan Ekonomi Universitas Negeri Gorontalo - Pradilia, Andi Desiah; Gani, Imam Prawiranegara (Jambura Arena Pengabdian, 2025)
This scientific writing training was designed to enhance the ability of students in the Department of Economic Education at Universitas Negeri Gorontalo to produce systematic and argumentative academic papers. The program employed a quantitative approach through a practice-based training method, emphasizing the structure of scientific writing, the use of academic language, and proper referencing techniques, aligned with the scientific writing guidelines of the Faculty of Economics and Business at Universitas Negeri Gorontalo. The implementation process comprised a planning phase, a series of intensive training sessions, and an evaluation of students’ written outputs. Descriptive quantitative analysis was used, incorporating observation sheets and assessments of the students' writing products. The results showed significant improvements in the structure of writing, the use of formal academic language, and the accuracy of citations. Overall, the program was found to be effective in developing fundamental scientific writing skills. It is recommended that similar initiatives be conducted on a sustainable basis, complemented by ongoing mentoring sessions and periodic evaluations.